2022
DOI: 10.3389/fphys.2022.840293
|View full text |Cite
|
Sign up to set email alerts
|

Three Classes of Antioxidant Defense Systems and the Development of Postmenopausal Osteoporosis

Abstract: Osteoporosis is a common bone imbalance disease that threatens the health of postmenopausal women. Estrogen deficiency accelerates the aging of women. Oxidative stress damage is regarded as the main pathogenesis of postmenopausal osteoporosis. The accumulation of reactive oxygen species in the bone microenvironment plays a role in osteoblast and osteoclast apoptosis. Improving the oxidative state is essential for the prevention and treatment of postmenopausal osteoporosis. There are three classes of antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 142 publications
(147 reference statements)
0
29
0
Order By: Relevance
“…Many factors, including fractures, may result in increased oxidative damage via inflammatory pathways and so on, which may consume the efficiency of the antioxidant defense system. 7 , 10 Therefore, we believe that the patients with high SOD or GR may have strong abilities to defend their bones from oxidative stress, and then are more likely to have a more satisfactory rehabilitation. Many studies had shown how the status of oxidative stress impacts bone remolding and bone healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors, including fractures, may result in increased oxidative damage via inflammatory pathways and so on, which may consume the efficiency of the antioxidant defense system. 7 , 10 Therefore, we believe that the patients with high SOD or GR may have strong abilities to defend their bones from oxidative stress, and then are more likely to have a more satisfactory rehabilitation. Many studies had shown how the status of oxidative stress impacts bone remolding and bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes can protect DNA, enzymes, and other cell structures from the damage of oxidative stress. 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our current study, the activities of CAT in the patients associated with osteoporosis (1.7±.0259 U/gHb) were lower relative to those in the controls (4.26±2.056 U/gHb). Deficiency of CAT is responsible for accumulation of hydrogen peroxide, which leads to oxidative damage on bones (Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the modulation of oxidative stress, several compounds behaving as antioxidants have been tested. From the broad list of antioxidants, vitamins such as C and E, frequently present in commercially available nutraceutical supplements, have been proposed for treating both osteoporosis [76] and osteoarthritis [77,78], simultaneously impacting positively on skeletal muscle mass and function [79]. Given that mitochondria are the main source of ROS, mitochondria-targeted compounds that reduce oxidative stress and improve cellular energy metabolism are desirable.…”
Section: Exercise Mimicking Drugs For the Treatment Of Musculoskeleta...mentioning
confidence: 99%